Ressonâncias entre as máscaras do historiador, do médico e do psicólogo: metamorfoses nietzschianas - Barbosa, Arlindo Antonio Araújo (2017)
This dissertation intends to delineate the task that Nietzsche gave himself and made the primary goal of presenting the “name” of Nietzsche. His act of rendering the project of transvaluation of all values effective, understood by the philosopher as the greatest demand yet made of humanity, considering that it provoked a deep cut in the history of Western man, was closely related to this approximation with the “name” of Nietzsche. Hence, the need for the philosopher to: make himself known. Still, how the author of Ecce homo “reveals” himself to humanity, fully distinguishing himself, is the way philosophers have presented themselves traditionally, in a type of presentation that distances itself from the idea of an autobiography. Thus, the author of Ecce homo presents himself through masks like the historian, the doctor and the psychologist, Nietzschean disguises that resonate with each other and are imbricated in the project of transvaluation of values. The thesis will demonstrate how some of the main aspects of his philosophy, such as forgetfulness, resentment, conscience, and values will be treated with these images, or by these masks put on by the philosopher